Server less Architecture: Optimizing Application Scalability and Cost Efficiency in Cloud Computing - Nisher Ahmed; Md Emran Hossain; S M Shadul Islam Rishad; Nur Nahar Rimi; Md Imran Sarkar (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Server less is recognized as one of the game changing technologies in cloud computing with large gains in scalability and cost to run applications. We explore the effect of Server less computing on these important facets in this paper. Server less platforms abstract away server management: Your applications can now scale automatically based on real-time fluctuations in demand which means no more manual provisioning and promise full resource utilization. However this is driven constantly, it indeed offers consistent high performance applications and in turn a very cost effective solution by eliminating idle time with the servers as well as operational overhead. Our objective is to trace the main attributes of Server less, namely event driven, statelessness, and micro services supported, and how these features provide scalability and cost optimization benefits. In addition, the paper explores the challenges and considerations of adopting Server less computing including vendor locking, security issues, and cold starts. This research presents detailed analyses of the pros and cons of the Server less architectures, bringing crucial insights into their ability to transform application scalability and cost savings when deployed in the cloud computing arena.